2010
DOI: 10.3233/ch-2010-1279
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of vessel age and early diagnose of atherosclerosis in progeria syndrome by using echo-tracking

Abstract: The stiffness of the arteries normally increases with age. Radiofrequency echo-tracking is a non-invasive ultrasound method which is able to detect the stiffness of the arteries, represented by the ␤ stiffness index. The estimation of biological age of vessels is possible on the basis of the normal age-group specific ␤ stiffness values.The ␤ stiffness index becomes higher in early stages of atherosclerosis as well, before any visible morphological changes. Hutchinson-Gilford progeria syndrome (HGPS) is rare ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…When motion is usually carried out at the standard time and frequency on no uniform, generally patients feel no fatigue tolerance to [8] . Through appropriate intensity aerobic exercise can effectively improve the patient's bone density at the same time within a certain range, the longer the time of patient motion, the higher the frequency the greater the stimulation of bone stress can effectively maintain and improve the content of bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…When motion is usually carried out at the standard time and frequency on no uniform, generally patients feel no fatigue tolerance to [8] . Through appropriate intensity aerobic exercise can effectively improve the patient's bone density at the same time within a certain range, the longer the time of patient motion, the higher the frequency the greater the stimulation of bone stress can effectively maintain and improve the content of bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ET technology can predict AS in CSF patients early and noninvasively. In addition, other diseases that affect arterial elasticity, such as Hutchinson-Gilford progeria syndrome [16], uremia [17], hyperuricemia [18], have been studied due to the popularity of ET technology, and satisfactory results have been obtained.…”
Section: Echo Tracking (Et) Techniquementioning
confidence: 99%
“…One of the first steps in atherosclerosis development is endothelial dysfunction, which is a state characterized by decreased arterial responsiveness to stimuli and increased arterial stiffness. Age and smoking, 2 risk factors for cardiovascular diseases, are associated with arterial stiffness [ 1 , 2 ]. Previous studies in humans showed that arterial stiffness could be beneficial for predicting the risk of cardiovascular diseases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…ET follows the phase shift in ultrasound frequency generated by vessel wall motion during the cardiac cycle, and automatically calculates indicators of arterial stiffness, such as stiffness parameter α, stiffness parameter β, arterial compliance (AC), distensibility coefficient (DC), and one-point pulse wave velocity (PWVβ). Previous studies have used ET to evaluate arterial function in patients with diabetes [ 8 10 ], hypertension [ 11 ], cardiovascular disease [ 12 ], Grave’s disease [ 13 ], and progeria [ 1 ] in patients receiving hemodialysis [ 14 ], in smoking individuals [ 2 ], and in normal individuals [ 15 ]; ET can also be used in animals. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%